ความสัมพันธ์ระหว่างทุนทางจิตวิทยา และความผูกพันต่อองค์การ ที่ส่งผลต่อพฤติกรรมการเป็นสมาชิกที่ดีต่อองค์การ ของข้าราชการในสังกัดองค์การบริหารส่วนจังหวัดปทุมธานี - ปลั่งกลาง นัยนา; สำรอง อริสา; ศรียงค์ มุกดา (Ph.D. in Social Sciences Journal, 2017)
การวิจัยเรื่อง ความสัมพันธ์ระหว่างทุนทางจิตวิทยา และความผูกพันต่อองค์การ ที่ส่งผลต่อพฤติกรรมการเป็นสมาชิกที่ดีต่อองค์การ ของข้าราชการในสังกัดองค์การบริหารส่วนจังหวัดปทุมธานี มีวัตถุประสงค์เพื่อ (1) ศึกษาระดับพฤติกรรมการเป็นสมาชิกที่ดีต่อองค์การ ทุนทางจิตวิทยา และความผูกพันต่อองค์การของข้าราชการในสังกัดองค์การบริหารส่วนจังหวัดปทุมธานี (2) ศึกษาความสัมพันธ์ระหว่างทุนทางจิตวิทยา ความผูกพันต่อองค์การ กับพฤติกรรมการเป็นสมาชิกที่ดีต่อองค์การของข้าราชการในสังกัดองค์การบริหารส่วนจังหวัดปทุมธานี (3) ศึกษาสมการทำนายพฤติกรรมการเป็นสมาชิกที่ดีต่อองค์การ ของข้าราชการในสังกัดองค์การบริหารส่วนจังหวัดปทุมธานี โดยมีทุนทางจิตวิทยา และความผูกพันต่อองค์การเป็นตัวทำนาย กลุ่มตัวอย่างที่ใช้ในการวิจัยครั้งนี้เป็นข้าราชการในสังกัดองค์การบริหารส่วนจังหวัดปทุมธานี จำนวน 257 คน เครื่องมือที่ใช้ในการวิจัยเป็นแบบสอบถาม 4 ส่วน คือ (1) แบบสอบถามข้อมูลส่วนบุคคล (2) แบบวัดพฤติกรรมการเป็นสมาชิกที่ดีต่อองค์การ (3) แบบวัดทุนทางจิตวิทยา (4) แบบวัดความผูกพันต่อองค์การ สถิติที่ใช้ในการวิเคราะห์ข้อมูล คือ ค่าความถี่ ค่าร้อยละ ค่าเฉลี่ย ส่วนเบี่ยงเบนมาตรฐาน ค่าสัมประสิทธิ์สหสัมพันธ์แบบเพียร์สัน และการวิเคราะห์ความถดถอยเชิงพหุคูณ โดยเลือกตัวแปรอิสระเข้าสมการด้วยวิธี Enter ผลการวิจัยพบว่า 1. ข้าราชการในสังกัดองค์การบริหารส่วนจังหวัดปทุมธานี ส่วนใหญ่เป็นเพศหญิง มีอายุ25-34 ปี มีอายุงาน 1-2 ปี และมีสถานภาพโสด พบว่า มีระดับพฤติกรรมการเป็นสมาชิกที่ดีต่อองค์การ และทุนทางจิตวิทยา อยู่ในระดับสูง ส่วนความผูกพันต่อองค์การ อยู่ในระดับปานกลาง 2. ทุนทางจิตวิทยา และความผูกพันต่อองค์การ มีความสัมพันธ์ทางบวกกับพฤติกรรมการเป็นสมาชิกที่ดีต่อองค์การ ของข้าราชการในสังกัดองค์การบริหารส่วนจังหวัดปทุมธานี อย่างมีนัยสำคัญทางสถิติที่ระดับ .05 เมื่อพิจารณารายด้านพบว่า ทุนทางจิตวิทยาทุกด้านมีความสัมพันธ์ทางบวกกับพฤติกรรมการเป็นสมาชิกที่ดีต่อองค์การทุกด้าน ส่วนความผูกพันต่อองค์การ พบว่า ความผูกพันต่อองค์การรายด้านมีความสัมพันธ์กับพฤติกรรมการเป็นสมาชิกที่ดีต่อองค์การเกือบทุกด้าน ยกเว้น ความผูกพันต่อองค์การด้านการคงอยู่และด้านบรรทัดฐานที่ไม่มีความสัมพันธ์กับพฤติกรรมการเป็นสมาชิกที่ดีต่อองค์การด้านการให้ความช่วยเหลือ 3. ทุนทางจิตวิทยา และความผูกพันต่อองค์การ สามารถทำนายพฤติกรรมการเป็นสมาชิกที่ดีต่อองค์การได้ร้อยละ 50.5 (R2 = .505) ได้อย่างมีนัยสำคัญทางสถิติที่ระดับ .05 โดยทุนทางจิตวิทยาสามารถทำนายพฤติกรรมการเป็นสมาชิกที่ดีต่อองค์การมากที่สุด รองลงมาคือ ความผูกพันต่อองค์การ THE RELATIONSHIPS BETWEEN PSYCHOLOGICAL CAPITAL AND ORGANIZATIONAL COMMITMENT AND ORGANIZATIONAL CITIZENSHIP BEHAVIORS OF PATHUM THANI PROVINCIAL ADMINISTRATION ORGANIZATION CIVIL OFFICIALS In this thesis, the researcher examines (1) the levels at which organizational citizenship behaviors, psychological capital, and the organizational commitment of Pathum Thani Provincial Administration Organization civil officials are evinced. The researcher also studies (2) the relationships between psychological capital, organizational commitment and the organizational citizenship behaviors of these civil officials. Finally, furthermore, the researcher frames (3) a predictive equation for the organizational citizenship behaviors of the civil officials with psychological capital and organizational commitment as predictors. The sample population consisted of 257 Pathum Thani Provincial Administration Organization civil officials. The research instrument was a quadripartite questionnaire consisting of (1) a sub-questionnaire eliciting data concerning demographical characteristics; (2) a form used to measure organizational citizenship behaviors; (3) a form utilized for measuring psychological capital; and (4) a form geared to measuring organizational commitment. Using techniques of descriptive statistics, the researcher analyzed the data collected in terms of frequency, percentage, mean, and standard deviation. The researcher also employed Pearson’s product moment correlation coefficient (PPMCC) method and multiple regression analysis (MRA) in the further analysis and extrapolation of the data collected. Findings are as follows: 1. The largest proportion of the civil officials were single females between the ages of twenty-five and thirty-four who had been employed from one to two years. They evinced high levels of organizational citizenship behaviors and psychological capital. However, they also displayed moderate levels of organizational commitment. 2. Psychological capital and organizational commitment were found to be positively correlated with the organizational citizenship behaviors of the civil officials at the statistically significant level of .05. When considered in each aspect, it was found that all aspects of psychological capital were positively correlated with all aspects of organizational citizenship behaviors. In regard to organizational commitment, it was found that each aspect of organizational commitment was correlated with organizational citizenship behaviors in almost all aspects, the exception being the aspect of retention. Moreover, it was determined that the aspect of norm was not correlated with organizational citizenship behaviors in the aspect of providing assistance. 3. The researcher determined that psychological capital and organizational commitment were predictive of organizational citizenship behaviors at 50.5 percent (R2 = 0.505) at the statistically significant level of .05. Psychological capital regressively exerted effects on organizational citizenship behaviors at the highest level. Next in descending order was organizational commitment.